A numerical investigation of the superbiphilic surface on the boiling curve using the volume of fluid method. (June 2021) - Lin, Chia-Wei; Lin, Yu-Chen; Hung, Tzu-Chen; Lin, Ming-Chieh; Hsu, Hua-Yi
Highlights: We investigate the effect of superbiphilic surface on boiling using the VOF method. The superbiphilic surface can enhance the heat transfer efficiency. The CHF obtained from superbiphilic surface is 55% greater than the hydrophilic/hydrophobic surface with a uniform CA. For the first time, the effect of biphilic contact angle on the complete boiling curve is shown. Abstract: In this work, a numerical simulation has been conducted to investigate the effect of superbiphilic surface on boiling using the volume of fluid (VOF) method. The boiling curve has been used to study the heat transfer efficiency and boiling dynamics which gain more physical insights into the underlying mechanisms. By adjusting the mixed hydrophilic and hydrophobic surface, two types of surface prpoerties have been investigated in this work: the superhydrophilic and superhydrophobic networks. The superhydrophilic network is found to achieve a larger critical heat flux and delay the occurrence of film boiling, while the superhydrophobic network can reach the critical heat flux at a comparatively lower superheat. The superbiphilic surface can enhance the heat transfer efficiency, and the critical heat flux obtained is 55 % greater than the hydrophilic/hydrophobic surface with a uniform contact angle. For the first time, the effect of superbiphilic contact angle on the complete boiling curve is shown. The numerical predictions demonstrate good agreement with prior experimental and theoretical studies. This work provides a better understanding of contact angle effect in boiling dynamics, and it serves a good indicator for designing a smarter heat exchanger which might greatly benefit the whole energy industry.